Internacionalizacion de la Mediana Empresa Familiar Ecuatoriana: El Rol de la Orientación a la Administración y la Flexibilidad estratégica del Equipo Gerencial - Andrade-Rodas, Esteban (2017)
Despite the importance of family business and itsdominant role in the world economy, the empirical knowledge about its internationalization is scarce, becoming evident in the literature with its necessity of being studied. Among the factors that motivate the internationalization, its orientation to the management and the strategic flexibility of its management team have been identified. Based on a sample taken in Ecuadorian family-owned medium-sized enterprises, this paper investigates the influence of the administrative orientation and the strategic flexibility of the management team in the export activity, which is evaluated by the level of internationalization. The outcomes reveal the presence of a positive relationship between these variables in the level of internationalization and, in addition, the orientation to the administration coupled with the strategic flexibility of the management team influence in a positive way the export activity. The results evince the importance of these factors in the internationalization of the Ecuadorian family-owned medium-sized enterprises, offering valuable elements for its management and survival.